Criticism of Capitalism in Upton Sinclair’s The Jungle - Farihatul Qamariyah; Tirmidi Tirmidi (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2026)
This study examines the critique of capitalism in Upton Sinclair’s The Jungle (1906) by integrating critical Discourse Analysis, narrative analysis, and intertextual analysis. The research aims to investigate how capitalism is criticized through language, narrative structure, characterization, and ideological discourse in the novel. By employing a qualitative research design, the study analyzes textual data related to labor exploitation, poverty, social injustice, class inequality, and power relations. The findings reveal that The Jungle portrays capitalism as an exploitative system. It prioritizes profit over human welfare. As a result, labor oppression, economic insecurity, social inequality, social alienation, and workers' dehumanization happen. Through its characters, the novel exposes the contradiction between the promise of the American Dream and the realities of industrial capitalism.  Furthermore, the novel also demonstrates that discourse and narrative strategies function as instruments for revealing ideological domination and normalizing exploitation. Finally, in the novel, Sinclair presents socialism as an alternative form of social awareness and resistance. It is concluded that The Jungle serves not only as a literary work but also as a powerful social critique that remains relevant to contemporary discussions of labor rights, inequality, and capitalist power structures.